Effect of Liuzijue Training on Balance and Respiratory Function of Stroke Patients in Recovery Stage - WANG Chen; ZHANG Peizhen; YANG Faming; YU Junwu (康复学报)
ObjectiveTo observe the effect of Liuzijue training on balance and respiratory function of stroke patients in recovery stage.MethodsA total of 63 stroke patients in recovery stage who were treated in the department of rehabilitation medicine of Haishu Rehabilitation Hospital (a teaching hospital of Ningbo college of Health Sciences) from January 2020 to March 2021, were recruited and randomly divided into control group and observation group, with 31 cases, 32 cases respectively. Both groups received conventional rehabilitation treatment such as physiotherapy and occupational therapy. Besides, the control group received core stability training while the observation group received Liuzijue training. Both groups received conventional rehabilitation treatment for 30 minutes a time, and core stability training or Liuzijue training for 20 minutes a time, once a day, five times a week, lasting for four weeks. The pronunciation order of the Liuzijue were "Xu, He, Hu, Si, Chui, Xi", and the training was conducted by nasal inhalation and oral exhalation, combined with movement guidance. Before and four weeks after treatment, Berg balance score (BBS) was used to evaluate the balance function; Fugl-Meyer assessment (FMA) was used to evaluate the motor functions; the modified Barthel index (MBI) was used to evaluate the activities of daily living; maximum phonation time (MPT) was used to evaluate the respiratory efficiency; color Doppler ultrasound was used to measure diaphragm thickness, mobility and diaphragm thickening fraction (DTF) and to evaluate diaphragm function.ResultsCompared with that before treatment, the BBS score, FMA score, MBI score, MPT, diaphragm thickness and mobility at quiet inspiration and at the end of maximum exhalation were significantly increased of both groups after treatment, the difference was statistically significant (P<0.05). Compared with the control group, the BBS score, MBI score, MPT, diaphragm mobility at quiet inspiration and at the end of maximum exhalation of the observation group after treatment were all significantly higher, and the difference was statistically significant (P<0.05), while there were no statistically significant differences in FMA score, DTF, diaphragm thickness at quiet inspiration and at the end of maximum exhalation (P>0.05).ConclusionLiuzijue training can effectively improve the balance function, activities of daily living, and respiratory function, and is recommended for clinical application.